Monitoring the Influence of Different Fluid Saturations Using Ultrasonic Velocity and Resistivity Measurement - Abd Hafidz, Muhammad Ashraff (2016)
Several number of techniques can be used to monitor the saturation, distribution and movement of fluids in the reservoir. Among of them are ultrasonic velocity and resistivity measurement which depends on fluid saturations, texture, mineral content and porosity of the subsurface. Monitoring of different fluid saturations using ultrasonic velocity alone is not very precise. Although ultrasonic velocity has better resolution efficiency in fluid mapping in geological reservoirs, but it is very poor in estimating fluid saturation accurately especially in high gas saturation regime. In the other hand, electrical resistivity has a better precision in quantifying relative saturation levels of immiscible fluids. By joint interpretation of resistivity and ultrasonic velocity, estimation and monitoring of injected fluid are possible.